Identification and characterization of Edwardsiella ictaluri from diseased Pangasius pangasius, cultured in Cirata Lake, Indonesia - MIRA MAWARDI; JAELANI JAELANI; ZAKKI ZAINUN; YUANI MUNDAYANA; BAIRD SAM CHILORA; ESTI HANDAYANI HARDI (Society for Indonesian Biodiversity, 2018)
Mawardi M, Jaelani, Zainun Z, Mundayana Y, Chilora BS, Hardi EH. 2018. Identification and characterization of Edwardsiella ictaluri from diseased Pangasius pangasius, cultured in Cirata Lake, Indonesia. Biodiversitas 19: 766-772. In January 2016, there were reported extensive mortalities of Pangasius pangasius cultured on cage, in Cirata Lake. Edwardsiella ictaluri is primarily recognized as a disease-causing pathogen in catfish species, causing an economically important bacterial infection hence affecting productivity of aquaculture enterprises in many regions across the E. ictaluri. The samples were 17 fishes collected from organs containing spleen, kidney, and liver. The total samples were 51 organs of fishes. The high bacteria infection prevalence level was found in kidney (29.41%). The gross pathological signs of sample of organs were abnormal sizes and abnormal color including white nodules. Bacteria were identified by conventional biochemical test, polymerase chain reaction (PCR) analysis and nucleotide sequencing. The results showed that P. pangasius cultured in cages in Cirata Lake is positively infected by E. ictaluri strain (accession number KF9071291). Other infection cases by Aeromonas sp. and Plesiomonas shigelloides as co-infection bacteria in P. pangasius were also found.